The Greek hospital and pharmacies of Smyrna (1723-1922) : Grčka bolnica i ljekarne u Smirni (1723. - 1922.) - Michaleas, Spyros N. (Array, 2021)
From the mid-18th century to the mid-20th century, Greek doctors in Smyrna collaborated with pharmacists, churches, and the city"s Greek Orthodox community to create a state of-the-art health network and charitable foundation to serve physical and mental health needs of the local community. At Graekikon Nosokomion o Agios Haralampos (Greek Saint Charalampos Hospital), or the Greek Hospital, every citizen, regardless of origin, language, religion, or economic status, had access to the most appropriate medical and pharmaceutical care. Neighborhood pharmacists complemented this care by administering vaccinations and preparing medicines. Smyrna"s pivotal influence on the Greek medical community ended in August 1922, when the Greek Hospital was destroyed during the Catastrophe of Smyrna.